Mandatory IFRS adoption and accounting comparability - Stefano Cascino; Joachim Gassen (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
The adoption of IFRS by many countries worldwide fuels the expectation that financial accounting might become more comparable across countries. This expectation is opposed to an alternative view that stresses the importance of incentives in shaping accounting information. We provide early evidence on this debate by investigating the effects of mandatory IFRS adoption on the comparability of financial accounting information around the world. Our results suggest that while mandatory adoption of IFRS increases the comparability of some prominent balance sheet line items across countries, it has no clear effect on the cross-country comparability of earnings attributes. To provide a rationale for these mixed findings, we investigate the IFRS measurement and disclosure compliance choices for a hand-collected sample of German and Italian firms. We find that predictable country-, region-, and firm-level incentives continue to shape the outcome of the financial reporting process and thus limit the crosssectional comparability of financial accounting information. Overall, our results suggest that the mandatory adoption of IFRS has a limited impact on accounting comparability and that accounting information continues to be shaped by both reporting standards and incentives.
Keywords: M41; G14; F42; 330; international accounting; IFRS; comparability; accounting harmonization; earnings attributes; disclosure determinants; accounting incentives; International Financial Reporting Standards; Publizitätspflicht; Bilanzierung; Vergleich; International; Welt